Aplicação do lean office na administração pública: Um estudo de caso em uma instituição federal de ensino superior - Elias, Laís Garcez Rocha (Universidade Federal de São Carlos, 2025)
Public administration follows norms, deadlines, and procedures, which stems from its roots in Max Weber's principles of operation and bureaucracy. These principles, centered on rationality, hierarchy, and cost-effectiveness, are designed to ensure fairness, consistency, and the efficient enforcement of rules, ultimately benefiting society as a whole. However, many public agencies are now adopting methodologies, tools, and practices from the private sector to address the dilemma of budget cuts while improving the services provided. The aim of this study is to apply Lean Office tools to the bidding process known as the Electronic Auction through the Price Registration System of the Federal University of Mato Grosso Foundation (FUFMT), in accordance with the changes brought by the New Public Procurement and Contracts Law, Law No. 14.133/2021. To achieve the proposed objective, a case study was conducted in the Procurement Management Coordination (CGC) of FUFMT, focusing on the bidding process in the Electronic Auction (PE) modality through the Price Registration System (SRP). Data for the study were collected through simple observation by the researcher, analysis of processes that originated the Price Registration Records in 2023, document analysis, an orientation questionnaire, and a focus group with a semi-structured guide involving the stakeholders of the process. In this context, the main contribution expected from the development of this study is to propose the improvement of public administration performance by eliminating waste, with the aid of Lean Office methodology, in compliance with legal requirements. With the collected data and applied tools, it was possible to develop the framework for the PE SRP process, with key points including raising awareness among requesting staff about their essential role, improvements in purchasing planning, the use of Preliminary Technical Study models and the Risk Matrix, as well as providing a pre-filled Terms of Reference and learning from previous processes. The creation of a response and action database to address recommendations from the Federal Attorney General’s Office, process standardization, and internal dispatches. Additionally, permanent actions are suggested, such as the creation and updating of Standard Operating Procedures (ETPs), guides, and best practices manuals, which will contribute to a faster and more accurate process flow.
Application of lean office in public administration: a case study in a federal higher institution
Keywords: Administração pública; Lean office; Aplicação de ferramentas; Public administration; Application of tools; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO